Mewujudkan Tata Kelola Desa Yang Partisipatif: Studi Kasus Pengelolaan Dana Desa Di Kabupaten Banggai - Amin, Muhamad; Nasution, Adnan (Pusat Penelitian Kebijakan Pembangunan, Universitas Hasanuddin, 2025)
Abstract This study aims to analyze the level of community participation in the utilization of Village Funds in Saiti Village, Nuhon District, Banggai Regency. The main focus of the study covers four aspects of participation, namely: planning, implementation, utilization of results, and evaluation of the use of Village Funds. This research approach is qualitative with data collection techniques through observation, in-depth interviews with village officials and the community, and documentation studies. Data analysis was carried out using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study show that the Saiti Village community shows active participation in almost all stages of Village Fund management. At the planning stage, participation is seen through the presence and proposals of residents in the Village Deliberation (Musdes) and the preparation of the Village Budget. At the implementation stage, the community is directly involved in physical development and empowerment activities, especially community leaders, youth, and religious leaders. However, women's participation, although quite visible, is still under the dominance of men. At the utilization stage, the community acknowledges the direct benefits of the Village Fund program, especially in the fields of infrastructure and social services. Evaluation and supervision are carried out through open forums and village government accountability reports, although not yet fully optimal. This study concludes that community participation in Saiti Village in managing the Village Fund is quite high, but still requires strengthening in terms of gender equality, policy socialization, and more equitable community involvement. Recommendations are directed at increasing the capacity of village institutions and inclusive participatory communication strategies. Abstrak Penelitian ini bertujuan untuk menganalisis tingkat partisipasi masyarakat dalam pemanfaatan dana desa di Desa Saiti, Kecamatan Nuhon, Kabupaten Banggai. Fokus utama penelitian mencakup empat aspek partisipasi, yaitu: perencanaan, pelaksanaan, pemanfaatan hasil, dan evaluasi penggunaan dana desa. Pendekatan penelitian ini bersifat kualitatif dengan teknik pengumpulan data melalui observasi, wawancara mendalam dengan perangkat desa dan masyarakat, serta studi dokumentasi. Analisis data dilakukan dengan menggunakan model interaktif yang meliputi reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa masyarakat Desa Saiti menunjukkan partisipasi aktif pada hampir seluruh tahapan pengelolaan dana desa. Pada tahap perencanaan, partisipasi terlihat melalui kehadiran dan usulan warga dalam Musyawarah Desa (Musdes) dan penyusunan APBDes. Pada tahap pelaksanaan, masyarakat terlibat langsung dalam kegiatan pembangunan fisik dan pemberdayaan, terutama tokoh masyarakat, pemuda, dan tokoh agama. Namun, partisipasi perempuan meskipun cukup terlihat, masih berada di bawah dominasi laki-laki. Pada tahap pemanfaatan, masyarakat mengakui adanya manfaat langsung dari program dana desa, terutama di bidang infrastruktur dan pelayanan sosial. Evaluasi dan pengawasan dilakukan melalui forum-forum terbuka dan laporan pertanggungjawaban pemerintah desa, meskipun belum sepenuhnya optimal. Penelitian ini menyimpulkan bahwa partisipasi masyarakat di Desa Saiti dalam pengelolaan dana desa cukup tinggi, namun tetap memerlukan penguatan dari sisi kesetaraan gender, sosialisasi kebijakan, dan pelibatan masyarakat secara lebih merata. Rekomendasi diarahkan pada peningkatan kapasitas kelembagaan desa dan strategi komunikasi partisipatif yang inklusif.